Patogenia experimental da infecção genital aguda e latente pelo herpesvírus bovino tipo 1.2 em bezerras - Henzel, Andréia (2008)
This study aimed at reproducting and characterizing the virological and clinico-pathological aspects of acute and latent genital infection by bovine herpesvirus type 1.2 (BoHV-1.2) in heifers. Four heifers were inoculated intravaginally with a Brazilian BoHV-1.2 isolate (SV-56/90) recovered from an outbreak of balanoposthitis. Virus inoculation (108.1TCID50/animal) resulted in efficient virus replication in the genital mucosa and the development of moderate to severe vulvovaginitis. The inoculated heifers shed virus in genital secretions in titers up to 107.3TCID50/mL until day 10 post infection (pi). Hyperemia, edema of vulvar and vestibular mucosa, vesicles, pustules and scabs were observed between days 1 and 10 pi. The vesicles and pustules increased in size and eventually coalesced and became covered with a mucopurulent and fibrinous exsudate. These signs increased in severity up to days 5 8 pi and progressively subsided thereafter. Dexamethasone administration at day 55 pi resulted in virus shedding in vaginal secretions of all heifers for up to 10 days. Virus reactivation was accompanied by genital signs resembling those observed during acute infection, yet less severe. Examination of the lumbar sacral ganglia and lymph nodes by PCR at day 36 postreactivation revealed the presence of latent viral DNA in the pudendal (4/4), genito-femoral, sciatic and rectal caudal (3/4) and obturator nerve ganglia (1/4); and in the sacral (3/4), deep inguinal, pre femoral, supramammary (2/4) and medial iliac lymph nodes (1/4). These results demonstrate that BoHV-1.2 DNA persists in sacral ganglia and regional lymph nodes during latency, and help in understanding the pathogenesis of acute and latent genital infection by BoHV-1.2.